Pollen‐derived nonallergenic substances enhance Th2‐induced IgE production in B cells. Issue 11 (28th August 2015) - Oeder, S.; Alessandrini, F.; Wirz, O. F.; Braun, A.; Wimmer, M.; Frank, U.; Hauser, M.; Durner, J.; Ferreira, F.; Ernst, D.; Mempel, M.; Gilles, S.; et al.
Abstract Background B cells play a central role in IgE‐mediated allergies. In damaged airway epithelium, they are exposed directly to aeroallergens. We aimed to assess whether direct exposure of B cells to pollen constituents affects allergic sensitization. Methods B cells from murine splenocytes and from blood samples of healthy donors were incubated for 8 days under Th2‐like conditions with aqueous ragweed pollen extracts (Amb‐APE) or its constituents. Secreted total IgM, IgG, and IgE was quantified by ELISA. Additionally, birch, grass, or pine‐pollen extracts were tested. The number of viable cells was evaluated by ATP measurements. B‐cell proliferation was measured by CFSE staining. IgE class switch was analyzed by quantitation of class switch transcripts. In an OVA/Alum i.p.‐sensitization mouse model, Amb‐APE was intranasally instilled for 11 consecutive days. Results Upon Th2 priming of murine B cells, ragweed pollen extract caused a dose‐dependent increase in IgE production, while IgG and IgM were not affected. The low‐molecular‐weight fraction and phytoprostane E1 (PPE1) increased IgE production, while Amb a 1 did not. PPE1 enhanced IgE also in human memory B cells. Under Th1 conditions, Amb‐APE did not influence immunoglobulin secretion. The IgE elevation was not ragweed specific. It correlated with proliferation of viable B cells, but not with IgE class switch. In vivo, Amb‐APE increased total IgE and showed adjuvant activity in allergic airway inflammation. Conclusions Aqueous pollen extracts, the protein‐free fraction of Amb‐APE, and the pollen‐contained substance PPE1 specifically enhance IgE production in Th2‐primed B cells. Thus, pollen‐derived nonallergenic substances might be responsible for B‐cell‐dependent aggravation of IgE‐mediated allergies.